Etika Sosial dan Spiritualitas Ekonomi Digital dalam Perspektif Muhammad Nejatullah Siddiqi pada Era Media Sosial - Zuhrul Anam; Tri Aldi Winata; Yoiz Shofwa Shafrani (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The rapid development of the digital economy and social media has fundamentally transformed the landscape of global economic interactions. However, this transformation has also triggered serious ethical issues, such as the prevalence of online fraud, aggressive materialist practices, loss of privacy, and the erosion of social cohesion due to unhealthy competition. This study aims to analyze the relevance of Muhammad Nejatullah Siddiqi's thoughts on social ethics and economic spirituality as a solution to the moral crisis in the context of the current digital era. This research utilizes a qualitative descriptive method with a library research approach, where data is collected from Siddiqi’s primary works and analyzed using content analysis to be contextualized with contemporary digital phenomena. The results indicate that Siddiqi's conceptual framework-anchored in Tawhid (unity of God), Adl (distributive justice), and Ukhuwah (universal brotherhood)-serves as a critical framework for mitigating the negative impacts of digital transactions. In this perspective, economic activities on social media must not merely act to maximize material profit but must also uphold spiritual values and the common good (maslahah). Siddiqi emphasizes that economic spirituality functions as an effective internal control mechanism to prevent exploitative and manipulative behavior. The study concludes that integrating Siddiqi’s ethical perspective into digital economic literacy is urgent to create a business ecosystem that is not only technologically efficient but also healthy, just, and humane.